The extension of website usability model and its evaluation criteria for Malaysia higher education institution - Nur Sukinah, Aziz (2019)
Website usability research is a consistently developing field. It has attracted many researchers based on their capabilities and constraints that are available for website usability. Even though there are many research about website usability, it devours the cause of inconsistency due to many websites usability aspects that offered by the researchers. There are lacks of research on website usability that focused on higher education institution website. It comprises the usability as the second order and satisfaction as mediator as well as the use of usability attributes such as content, navigation, learnability, accessibility, interface design and satisfaction to measure the higher education institution websites. In this sense, it is important to identify the constructs when assessing the higher education institution website usability in order to be able to design decent usability guidelines that support the measurement instrument and hence generate better results. The research is carried out to propose the extension of website usability model that has element of mediator and second order in the model. There are few constructs that are identified to evaluate the website usability such as effectiveness, efficiency, accessibility, learnability, satisfaction, navigability, content, interface design and intention to use. A mixed method that included qualitative and quantitative approach were used in this study. Interview with experts are conducted to obtain a better view about the model and construct in the research. Then, the instrument is needed to undergo content validity examination by experts, pre-test and pilot test to be utilized for assessment of the instrument. The final instrument of website usability, namely the Questionnaire Website Usability (QWU) that have 9 constructs and 45 items of questionnaire to evaluate the website and validate the extension website usability model were strengthened through a study conducted on 654 respondents. The data analysis using Partial Least Square – Structural Equation Modeling (PLS-SEM) to test the relationship between constructs in this research. The research has found that the usability has a significant relationship with satisfaction and in turn, satisfaction has a significant relationship to the intention to use. Based on the measurement model for usability as second order shows that all requirements are fulfiled and significant. The findings have also discovered that the satisfaction is mediated between usability and intention to use. The finding contributes to the knowledge in the field of website usability. It has demonstrated that satisfaction as a mediator plays a vital role in a website usability model. This has been shown by the user perception on the website that they have used. The website usability attributes as a second order makes the model simpler and reduces the complexity of the model. The extension model contributes to the development of additional theoretical linkages which is between usability construct, satisfaction and intention to use. In conclusion, the total of 9 constructs and 45 items of the website usability model are identified and validated as the main attributes to be used in evaluating website usability. The findings of this research also could be used by website developer and government agencies to develop a better plan to enhance the website usability.